A Qualitative Study of Prevention and Intervention Policies on Sexual Violence Against Children in Cirebon City - Teguh Widodo; Mario Ekoriano; Afifah Afifah; Frida Kurniawati (International Seminar on Social Work Update, 2023)
This study is motivated by an increasing trend of child sexual abuse recently in Indonesia.  The initial assumption is that the rampant incidence of sexual abuse is due to the non-optimality of the eight family functions. This study aims to analyze how child sexual abuse prevention and intervention policies are carried out by local governments. This research is qualitative, taking samples regionally in Cirebon City. Data were collected through social worker reports when a case response occurs.  Confirmation was carried out to check the truth of the incident and observe the condition of the victim and his family.  The analysis was carried out by looking at the case records carried out by social workers. Focus group discussion to obtain information on various programs and activities carried out by the local government related to the efforts of preventing sexual child abuse.  The results showed that intervention efforts have been carried out by both local government and community elements. There were overlaps in their duties and functions.  The causes of sexual child abuse were carried out by people who were the closest to the victim’s relative.  The first sexual experience and so on will have an impact on the possibility of a further sensation of the next sexual stimulation. Most of the victims have only a single parent either a mother or father. They were alive or died in divorce so they lose the figure of his/her parents' profile as a protective person. This study recommends that sexual violence prevention policies should be integrated into the relief process. Prevention of sexual violence against children prioritizes the improvement of eight family functions by emphasizing family resilience. Keywords: child sexual abuse, family resilience, child sexual violence, parenting